2018
DOI: 10.4067/s0718-58392018000100003
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria strains as promoters of rooting in hybrids of Eucalyptus nitens × Eucalyptus globulus

Abstract: In Chile, the Eucalyptus nitens (H. Deane & Maiden) Maiden × E. globulus Labill. hybrid presents the highest production potential due to its desirable characteristics for the production of cellulose. Nevertheless, its low ability to rooting complicates the clonal propagation in nurseries, with the need for new alternatives to increase rooting. The objective of this research was to evaluate the effect of rhizobacteria in the adventitious rooting of mini-cuttings of two hybrid E. nitens × E. globulus clones, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Results derived from in vitro validation using A. thaliana, also demonstrated clear effects of rhizobacteria inoculation on root architecture. Similar morphological changes in response to rhizobacteria inoculation have been reported in a wide number of tropical tree species as Cedrela fissilis [16], Acacia auriculiformis [19], Cecropia pachystachya, Heliocarpus popayanensis Trema micrantha, Cabralea canjerana, Cariniana estrellensis, Trichilia elegans [32], Eucalyptus nitens [33], Jatropha curcas [34] and others. Reported changes in root architecture are associated with the modulation of cell division and the differentiation of the apical meristem and lateral root primordia sites [35].…”
Section: Discussionsupporting
confidence: 77%
“…Results derived from in vitro validation using A. thaliana, also demonstrated clear effects of rhizobacteria inoculation on root architecture. Similar morphological changes in response to rhizobacteria inoculation have been reported in a wide number of tropical tree species as Cedrela fissilis [16], Acacia auriculiformis [19], Cecropia pachystachya, Heliocarpus popayanensis Trema micrantha, Cabralea canjerana, Cariniana estrellensis, Trichilia elegans [32], Eucalyptus nitens [33], Jatropha curcas [34] and others. Reported changes in root architecture are associated with the modulation of cell division and the differentiation of the apical meristem and lateral root primordia sites [35].…”
Section: Discussionsupporting
confidence: 77%
“…Thereafter samples were diluted and plated on potato dextrose agar (PDA) and R2A agar using an easySpiral ® Pro automatic plater (interscience, Saint Nom, France). Plates were incubated at 25 • C for 48 h. After incubation, representatives of bacterial colonies presenting different morphological variations (colour, shape, and size) were isolated and purified by sequentially streaking single colonies onto fresh agar plates [31,32]. Purified isolates were cryo-preserved at −80 • C in a Microbank™ (Pro-Lab Diagnostics, Bromborough, UK).…”
Section: Isolation Of Rhizospheric Bacteriamentioning
confidence: 99%
“…On the other hand, many studies have showed that inoculation of plants with PGPR such as B. subtilis improves plant growth, yield and nutrient uptake under salt stress conditions (Abdel-Rahman et al, 2011, Mohamed & Gomaa, 2012and Abd Allah et al, 2017. In addition, PGPR in the genera of Bacillus, Agrobacterium, Azospirillum and Pseudomonas have recently been used to induce adventitious root formation in stem cuttings (Abdel-Rahman &El-Naggar, 2014 andGonzález et al, 2018). These bacteria are able to exert a beneficial effect upon plant growth such as increases root growth and root weight (Karakurt et al, 2009 andAbdel-Rahman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%